Control of a rehabilitation robot - Lin, Wei. (2012)
The objective of this project is to design a rehabilitation robot arm system which can provide more efficient trainings for patients with stroke to reinforce the muscles of the upper limb. This helps in making the patients gain confidence and physically competent.